Dampak Onsite Training Model (OTM) Terhadap Peningkatan Pendapatan Petani - Wibowo, Ady; Setiawan, Iwan; Noor, Trisna Insan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Farming is very dependent on the ability of farmers as the main manager. Farmers as humans have the freedom to interact with the environment around them, learn new things, and follow any existing developments in order to increase the scale of their farming so that it can have an impact on increasing their welfare. The pattern of training that has been carried out so far is not in accordance with the latest conditions and challenges. Current training is only limited to increasing the knowledge and attitude of farmers, not directly correlated with increasing farmer income which leads to farmer welfare. In line with this, a form of training that is adaptive to the times and can be easily accepted by farmers is needed. Breakthroughs and innovation creations both in materials and methods in conducting training for farmers need to be carried out in order to answer various human resource problems for farmers. Answering this thought, the Onsite Training Model (OTM) is here as a solution and a breakthrough in training and improving farmer human resources. This study aims to analyze the impact of the Onsite Training Model (OTM) on vegetable agribusiness training on farmers' income. Respondents in this study were 45 farmers who attended the training. For this reason, quantitative descriptive analysis was used, analysis of farm income and different comparison tests using the paired sample t test. The results showed that the farmers' income after attending the training was greater and significantly different than the income before attending the training. Therefore farmers are expected to continue to consistently apply the knowledge gained from training using the Onsite Training Model (OTM).